Reproduction-Related Sound Production of Grasshoppers Regulated by Internal State and Actual Sensory Environment - Heinrich, Ralf; Kunst, Michael; Wirmer, Andrea (Frontiers in Neuroscience, 2012)
The interplay of neural and hormonal mechanisms activated by entero- and exteroreceptors biases the selection of actions by decision making neuronal circuits. The reproductive behaviour of acoustically communicating grasshoppers, which is regulated by short-term neural and longer-term hormonal mechanisms, has frequently been used to study the cellular and physiological processes that select particular actions from the species-specific repertoire of behaviours. Various grasshoppers communicate with species- and situation-specific songs in order to attract and court mating partners, to signal reproductive readiness or to fend off competitors. Selection and coordination of type, intensity and timing of sound signals is mediated by the central complex, a highly structured brain neuropil known to integrate multimodal pre-processed sensory information by a large number of chemical messengers. In addition, reproductive activity including sound production critically depends on maturation, previous mating experience and oviposition cycles. In this regard, juvenile hormone released from the corpora allata has been identified as a decisive hormonal signal necessary to establish reproductive motivation in grasshopper females. Both regulatory systems, the central complex mediating short-term regulation and the corpora allata mediating longer-term regulation of reproduction related sound production mutually influence each other’s activity in order to generate a coherent state of excitation that promotes or suppresses reproductive behaviour in respective appropriate or inappropriate situations. This review summarizes our current knowledge about extrinsic and intrinsic factors that influence grasshopper reproductive motivation, their representation in the nervous system and their integrative processing that mediates the initiation or suppression of reproductive behaviors.